Uji Antagonistik Bakteri Penghasil Indole Acetic Acid Terhadap Jamur Helminthosporium maydis Secara In Vitro - TAMPUBOLON, HELENA; KHALIMI, KHAMDAN; PHABIOLA, TRISNA AGUNG (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.11, No.4, Oktober 2022, 2023)
Antagonistic Test of Indole Acetic Acid Producing Bacteria Against Helminthosporium maydis In Vitro Helminthosporium maydis is the cause of important diseases in maize, including leaf blight. Leaf blight is the most dominant disease because it causes large losses. The use of biological agents is one way to treat leaf blight that is environmentally friendly. One of these biological agents is IAA-producing bacteria. This research was conducted in vitro . The results showed that there were several IAA-producing bacteria that were able to inhibit the growth of H. maydis in vitro with the highest inhibition in the treatment of B. thuringiensis GR12 isolates of 96.44% when compared to controls. IAA-producing bacteria were able to inhibit the growth of H. maydis biomass with the percentage of inhibition ranging from 73.97% - 80.82%. The treatment of IAA-producing bacterial filtrate at a concentration of 20%-90% was able to inhibit the growth of H. maydis colonies in vitro. The results of this study indicate that IAA compounds produced by bacteria are antifungal.